Theoretical and experimental study on thermodynamic performance of single screw refrigeration compressor with Multicolumn Envelope Meshing Pair. (25th June 2016) - Wang, Zengli; Wang, Zhenbo; Wang, Jun; Jiang, Wenchun; Feng, Quanke
Highlights: Theoretical model was established to predict the performance of SSRC with MEMP. Experiments prove that SSRC with MEMP has higher volume displacement. Thermodynamic performances of the SSRC with MEMP have been analyzed. Theoretical model was validated to have reasonable error by experimental study. SSRC with MEMP is proved high volumetric efficiency and more power consumption. Abstract: In single screw refrigeration compressor (SSRC), the Multicolumn Envelope Meshing Pair (MEMP) was proposed to reduce the wear of the meshing pair. However, the application of this new type meshing pair will change the thermodynamic performance of SSRC. It is necessary to research the thermodynamic performance of the SSRC with MEMP to evaluate the value of the proposed MEMP. In this paper, a theoretical calculation model describing the working process of the SSRC with MEMP is established to predict the thermodynamic performance of the SSRC. Experimental investigations on the performance of a SSRC with MEMP under different conditions are also carried out to verify the theoretical calculation model. Obtained results show that the theoretical calculation results are in good agreement with the experimental ones, which means that the presented theoretical calculation model is a powerful tool for performance analysis of the SSRC with MEMP. With the validated model, thermodynamic performances of the SSRC with MEMP have been analyzed. The SSRC with MEMP is proved to have high volume displacement and volumetric efficiency but needs slightly more shaft power. The maximum increment of shaft power and volumetric efficiency of SSRC with MEMP is 5.06% and 3.7% respectively in all working conditions.